IoT-based weather station with air quality measurement using ESP32 for environmental aerial condition study - Prisma Megantoro; Shofa Aulia Aldhama; Gunawan Setia Prihandana; P. Vigneshwaran (TELKOMNIKA (Telecommunication Computing Electronics and Control), 2021)
This article discusses the design of a weather station device that also functions to measure the concentration of gases in the air. This real-time telemetry device based on the internet of things (IoT) uses the ESP32 board to process measurement data. Some of the weather parameters measured are wind speed, wind direction, humidity, ambient air temperature, air pressure, rainfall, and ultraviolet (UV) index. Meanwhile, the gas concentration parameters in the air are ozone, hydrogen, methane, ammonia, carbon monoxide, and carbon dioxide. The readings from all sensors are processed by the ESP32 board and uploaded to the server. Then a client device will receive the data set and then processed, displayed on the monitor, and stored in the form of a text file. Furthermore, the monitor and the data are used for the analysis of the surrounding air quality and weather conditions.